Critical Annealing Temperature for Stacking Orientation of Bilayer Graphene. Issue 39 (30th August 2018) - Zhu, Zhenwei; Zhan, Linjie; Shih, Tien‐Mo; Wan, Wen; Lu, Jie; Huang, Junjie; Guo, Shengshi; Zhou, Yinghui; Cai, Weiwei
Abstract: It is rarely reported that stacking orientations of bilayer graphene (BLG) can be manipulated by the annealing process. Most investigators have painstakingly fabricated this BLG by chemical vapor deposition growth or mechanical means. Here, it is discovered that, at ≈600 °C, called the critical annealing temperature (CAT), most stacking orientations collapse into strongly coupled or AB‐stacked states. This phenomenon is governed (i) macroscopically by the stress generation and release in top graphene domains, evolving from mild ripples to sharp billows in certain local areas, and (ii) microscopically by the principle of minimal potential obeyed by carbon atoms that have acquired sufficient thermal energy at CAT. Conspicuously, evolutions of stacking orientations in Raman mappings under various annealing temperatures are observed. Furthermore, MoS2 synthesized on BLG is used to directly observe crystal orientations of top and bottom graphene layers. The finding of CAT provides a guide for the fabrication of strongly coupled or AB‐stacked BLG, and can be applied to aligning other 2D heterostructures. Abstract : Random stacking orientations of bilayer graphene at critical annealing temperature can evolve into AB‐stacked or strongly‐coupled states. This phenomenon is governed (i) macroscopically by the stress generation and release in top graphene, and (ii) microscopically by the principle of minimal potential obeyed by carbon atoms. Our findings provide the guidance of fabricating large‐area bilayer graphene and other aligned two‐dimensional heterostructures.